2022
DOI: 10.3390/molecules27217653
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid: A Natural Phenol That Inhibits Neoplastic Events through Modulation of Oncogenic Signaling

Abstract: Despite the immense therapeutic advances in the field of health sciences, cancer is still to be found among the global leading causes of morbidity and mortality. Ethnomedicinally, natural bioactive compounds isolated from various plant sources have been used for the treatment of several cancer types and have gained notable attention. Ferulic acid, a natural compound derived from various seeds, nuts, leaves, and fruits, exhibits a variety of pharmacological effects in cancer, including its proapoptotic, cell-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 90 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…It is more soluble in dimethylformamide, ethyl acetate and alcoholic solvents than in water (0.91 mg/mL, logP = 1.51). 24,25 It generates a phenoxyl radical that is resonancestabilized. However, this substance is only stable up to 150 °C and completely degrades above 226 °C.…”
Section: Physical Properties and Chemistry Of Hydroxycinnamic Acid De...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is more soluble in dimethylformamide, ethyl acetate and alcoholic solvents than in water (0.91 mg/mL, logP = 1.51). 24,25 It generates a phenoxyl radical that is resonancestabilized. However, this substance is only stable up to 150 °C and completely degrades above 226 °C.…”
Section: Physical Properties and Chemistry Of Hydroxycinnamic Acid De...mentioning
confidence: 99%
“…However, this substance is only stable up to 150 °C and completely degrades above 226 °C. 24 Ferulic acid is distinguished from other compounds by the presence of a carboxyl group and hydroxyl as well as methoxy groups. 16 The double bond between C2−C3 and the hydroxyl groups at C1 and C9 of ferulic acid are thought to be the primary sources of the compound's effective bioactivity and antioxidant capabilities, respectively.…”
Section: Physical Properties and Chemistry Of Hydroxycinnamic Acid De...mentioning
confidence: 99%
See 1 more Smart Citation
“…It rarely occurs in a free state and is typically conjugated with mono, oligosaccharides, polysaccharides, polyamines, and lipids. Multiple studies have shown a wide range of biological effects by FA against clinical conditions, including, cancer, diabetes, lung, and cardiovascular diseases [ 108 , 152 , 153 ]. It also shows hepatic, neuro, and photoprotective effects.…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
“…FA had been proposed as a promising anticancer agent with potential therapeutic benefits that include antiproliferative, proapoptotic, antiangiogenic, and/or antimetastatic effects in different experimental cancer models influencing multiple molecular targets and cellular signaling pathways [ 108 ]. Karimvand et al [ 155 ] reported a significant increase in apoptosis index characterized by decreased Bcl-2 expression and higher Bax expression after FA treatment in renal carcinoma.…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%